1998
DOI: 10.1007/s002530051206
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production using nuclear petite yeast mutants

Abstract: Two respiratory-deficient nuclear petites, FY23 delta pet191 and FY23 delta cox5a, of the yeast Saccharomyces cerevisiae were generated using polymerase-chain-reaction-mediated gene disruption, and their respective ethanol tolerance and productivity assessed and compared to those of the parental grande, FY23WT, and a mitochondrial petite, FY23 rho(0). Batch culture studies demonstrated that the parental strain was the most tolerant to exogenously added ethanol with an inhibition constant, Ki, of 2.3% (w/v) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 0 publications
4
26
0
Order By: Relevance
“…However, it is also reported that functional mitochondria are essential to maintain the tolerance to ethanol and, hence, a high growth rate (Hutter and OliverS.G., 1998). Also in our case, despite the increased ATP production, AF treated cells slowdown the growth rate after 6 h. All these data strengthen the idea of mitochondria as AF target.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, it is also reported that functional mitochondria are essential to maintain the tolerance to ethanol and, hence, a high growth rate (Hutter and OliverS.G., 1998). Also in our case, despite the increased ATP production, AF treated cells slowdown the growth rate after 6 h. All these data strengthen the idea of mitochondria as AF target.…”
Section: Discussionsupporting
confidence: 75%
“…damages enable the achievement of a fermentation rate higher than in wild-type strains (Hutter and OliverS.G., 1998). However, it is also reported that functional mitochondria are essential to maintain the tolerance to ethanol and, hence, a high growth rate (Hutter and OliverS.G., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory status of the two FL-resistant mutant isolates was investigated on yeast extractpeptone-glycerol medium containing 1 % (w/v) yeast extract, 2 % (w/ v) peptone and 3 % (w/v) glycerol as the sole carbon source (Hutter & Oliver, 1998). Thus, cells unable to respire were negatively selected on this medium.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have pointed out the potential of utilizing respiration-deficient nuclear petites for the commercial production of ethanol (8,13). Despite the vast number of strategies adopted for the construction of amylolytic strains of S. cerevisiae, there have been no reports about the application of respiration-deficient nuclear petites for the production of ethanol from starch.…”
mentioning
confidence: 99%
“…The 100%-respiration-deficient nuclear petite FY23⌬pet191 mutant of the parental haploid S. cerevisiae FY23 strain (MATa ura3-52 trp⌬63 leu2⌬1) (19) was generated using PCR-mediated disruption of the pet191 gene with a kanMX4 disruption cassette that determines G418 sulfate (Geneticin) resistance in yeast (8). The S. cerevisiae NPB-G strain was generated by transforming (17) the FY23⌬pet191 strain with the pPB-G plasmid (5), which contains the B. subtilis ␣-amylase and the A. awamori glucoamylase genes expressed under the control of the PGK1 promoter as an excreted fusion protein.…”
mentioning
confidence: 99%